Evaluating Chaco migration scenarios using dynamic social network analysis. (22nd August 2018) - Mills, Barbara J.; Peeples, Matthew A.; Aragon, Leslie D.; Bellorado, Benjamin A.; Clark, Jeffery J.; Giomi, Evan; Windes, Thomas C.
Abstract : Migration was a key social process contributing to the creation of the 'Chaco World' between AD 800 and 1200. Dynamic social network analysis allows for evaluation of several migration scenarios, and demonstrates that Chaco's earliest ninth-century networks show interaction with areas to the west and south, rather than migration to the Canyon from the Northern San Juan. By the late eleventh century, Chaco Canyon was tied strongly to the Middle and Northern San Juan, while a twelfth-century retraction of networks separated the Northern and Southern San Juan areas prior to regional depopulation. Understanding Chaco migration is important for comprehending both its uniqueness in U.S. Southwest archaeology and for comparison with other case studies worldwide.